Exploring spatial network structures in entrepreneurial ecosystems: a network and clustering analysis of global venture funding flows - Lance Christian (Small Business Economics, 2025)
This study examines the interconnectedness of entrepreneurial ecosystems (EEs) through a comprehensive geospatial network analysis of global investment flows. Addressing the critical need to explore EEs beyond their local boundaries, we investigate how EEs interact across regional, national, and international levels. Utilizing data from Crunchbase, which details 556,612 investment interactions among 5488 city-regions globally from 2000 to 2022, our analysis employs network topology analysis and hierarchical clustering to elicit similarities and differences in the financial interconnectedness. Our findings reveal significant variability in how EEs are connected, with distinct patterns emerging among clusters. We highlight the role of external linkages in shaping the structure EEs, challenging the inward-focused perspective commonly held in current literature. Notably, our research uncovers the extensive reach and complexity of EEs' financial interactions, illustrating both concentrated and dispersed network embeddedness. The study contributes to the entrepreneurial ecosystem literature in three ways. First, we extend the analysis of EEs to consider their spatial interconnectedness and complex network structures. Second, we introduce network topology analysis as a robust method for understanding the complexities of EE connectivity. And third, through hierarchical clustering of EEs by their network metrics, we show that EE vary greatly in their relational structures. These insights not only enrich our understanding of EEs but also inform policy implications, suggesting avenues for fostering stronger, more resilient entrepreneurial environments through strategic network facilitation and international cooperation.
Keywords: L26; R12; C55; O52; R58; F63; R11; 330; Entrepreneurial ecosystems; Economic geography; Spatial network analysis; Longitudinal study; Evolutionary economics; Complex adaptive systems